Racial Disparities in Nutritional Risk among Community-Dwelling Older Adults in Adult Day Health Care. Issue 4 (2nd October 2019) - Sadarangani, Tina R.; Missaelides, Lydia; Yu, Gary; Trinh-Shevrin, Chau; Brody, Abraham
Abstract: Information regarding nutritional risk among users of American adult day health centers (ADHCs), 60% of whom are racial minorities, is scant. This study examined nutritional risk and associated factors in a diverse sample ADHC users aged 50+ using secondary cross-sectional analysis of data collected between 2013 and 2017. Risk was assessed using the DETERMINE checklist, and results were stratified by race. The majority of the sample ( N = 188) was at moderate (45.2%) or high (38.5%) nutritional risk, with statistically significant racial differences. Blacks were at greater risk than any other group: 65% had high nutritional risk; 76.5% ate <5 servings of fruits, vegetables, or milk daily; 21% ate <2 meals daily, 48.5% reported involuntary weight loss/gain, and 41.2% had tooth loss/mouth pain. Older adults in ADHCs are at elevated risk of malnutrition, disproportionately so amongst blacks. Both routine nutrition screening and population-specific approaches are needed to attenuate risk.